The Effect of Alkalization Duration on the Tensile Properties of Starch-Based Bioplastic Reinforced with Water Hyacinth Fiber (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
Nowadays, many researchers are studying bioplastic fabrication to address conventional plastic limitations. This study investigated the effect of water hyacinth fiber (WHF) alkalization duration on the tensile properties of produced bioplastics. The dried WHF was soaked in a 10% NaOH solution at 40°C for durations of 1, 2, 3, 4, and 5 hours. Following this, bioplastics were fabricated by mixing cassava starch (CS), WHF, and glycerol by using the melt intercalation method. FTIR characterization results revealed a strong-broad absorption band at 3288 cm-1 and a medium-sharp band at 1419 cm-1. These findings confirm the hydrogen interaction between the hydroxyl groups on the fiber surface and the matrix. The tensile strength of the bioplastics increased with the duration of WHF delignification. Notably, bioplastics fabricated with WHF delignified for 5 hours exhibited the highest tensile strength, reaching 1.349 MPa. Therefore, the duration of WHF delignification directly impacts the tensile strength of the bioplastics.